Molecular Weight Impact of Poly(2,5-Benzimidazole) Polymer on Film Conductivity, Ion Exchange Capacity, Acid Retention Capability, and Oxidative Stability - Berber, Mohamed R. (Frontiers in Energy Research, 2020)
In order to show the impact of the molecular weight (MW) of poly(2,5-benzimidazole) (ABPBI) on its physicochemical properties, a series of ABPBI polymers with different MWs ranging from 20 to 113 KDa were synthesized, and fabricated into conductive films. The ABPBI films characterized by different spectroscopic methods, measuring the acid loading level, acid retention capability, ion exchange capacity (IEC), and the proton conductivity. Notably, the phosphoric acid (PA) loading ratio increased with the increase of ABPBI MW. The acid retention capability increased by 11% when the ABPBI MW reached 113 KDa. The fabricated ABPBI films exhibited good oxidative stability. A weight loss of only 9 wt% observed for the high MW ABPBI film compared to 19 wt% for the low MW ABPBI film after 7 days in Fenton’s reagent at 65 °C. The Ion exchange capacity (IEC) increased with an order of magnitude when the ABPBI MW changed from 20 to 113 KDa. A maximum proton conductivity of 8.0 mS/cm was recorded for the high MW film at 140 °C, which was 45% higher than that the low MW ABPBI film. The proton conduction process followed the Grotthuss mechanism with a low activation energy (9.3 kJ/ mol) at the high MW ABPBI film. These results indicated how important is the ABPBI MW in obtaining conductive films with remarkable properties for fuel cell (FC) applications. Prospectively, the findings of the current study can be implemented for the other conductive polymers.